Bioconversion of black soldier fly (Hermetia illucens) on agricultural waste: Potential source of protein and lipid, the application (A mini-review) - Hidayat, Nur; Anggarini, Sakunda; Sabrina Sunyoto, Nimas Mayang; Fitri, Loeki Enggar; Suhartini, Sri; Rohma, Novita Ainur; Elviliana, Elviliana; Arif Setyawan, Sang Aji; Subekti, Indah Fitriana; Namira, Anggi Alya; Nafi’ah, Riris Waladatun; Afifah, Firdiani Nur; Pratama, Andhika Putra Agus (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Hermetia illucens, well-known as black soldier fly (BSF), is an insect easily found in subtropical and tropical regions. It contains high protein and lipids. BSF is known as one of the biological agents consuming organic components, thus having a high potential to overcome organic waste problems. BSF has promising advantages due to its long development time in the larval stage (compared to other flies) and its ability to self-separate from organic waste. BSF with large protein and lipid content can substitute the commonly used protein source in aquaculture, poultry and livestock compound diet formulation, which can be an option to overcome limited sources of future food and feed insecurity. This review analyses the latest study of bioconversion using BSF from the viewpoint of nutrient composition, degradation rate and biomass results from different feed treatments. Various feed and growth mediums have been studied to obtain high protein and lipid biomass. Hopefully, the information will provide new research directions and solutions for converting agro-industrial waste using bioconversion with BSF.